2022
DOI: 10.3390/insects13090792
|View full text |Cite
|
Sign up to set email alerts
|

Parasitism by the Tachinid Parasitoid Exorista japonica Leads to Suppression of Basal Metabolism and Activation of Immune Response in the Host Bombyx mori

Abstract: The dipteran tachinid parasitoids are important biocontrol agents, and they must survive the harsh environment and rely on the resources of the host insect to complete their larval stage. We have previously demonstrated that the parasitism by the tachinid parasitoid Exorista japonica, a pest of the silkworm, causes pupation defects in Bombyx mori. However, the underlying mechanism is not fully understood. Here, we performed transcriptome analysis of the fat body of B. mori parasitized by E. japonica. We identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 53 publications
1
11
0
Order By: Relevance
“…Additionally, scavenger receptors and hemocytins were highlighted after M. manilae parasitization. This result resonated with the findings that wasp parasitism perturbed the expressions of the genes implicated in the host humoral immune response [ 68 , 69 , 70 ]. We randomly selected several immune-related DEGs for qPCR verification, which showed a similar trend in expression patterns with the high throughput sequencing data in response to wasp parasitization.…”
Section: Discussionsupporting
confidence: 77%
“…Additionally, scavenger receptors and hemocytins were highlighted after M. manilae parasitization. This result resonated with the findings that wasp parasitism perturbed the expressions of the genes implicated in the host humoral immune response [ 68 , 69 , 70 ]. We randomly selected several immune-related DEGs for qPCR verification, which showed a similar trend in expression patterns with the high throughput sequencing data in response to wasp parasitization.…”
Section: Discussionsupporting
confidence: 77%
“…Drosophila melanogaster can activate humoral immunity and upregulate the expressions of AMPs and stress proteins against parasitoid wasps (Benassi et al, 2000; Yang et al, 2019). Previous studies have shown that when E. japonica parasitizes the silkworm, the AMPs of the silkworm fat body are significantly upregulated (M. Dai et al, 2022; M. L. Dai et al, 2022). This study found that the expressions of AMPs in the midgut of the silkworm were upregulated and then downregulated from the 1st to the 3rd day of parasitism, indicating that the midgut immunity of the silkworm was activated at the initial stage of parasitism, actively resisting the invasion of E. japonica .…”
Section: Discussionmentioning
confidence: 99%
“…The variety of silkworms used in the present study was “Jingsong × Haoyue,” which was kept by our laboratory. The tachinid E. japonica was bred in our laboratory for generations (M. Dai et al, 2022; M. L. Dai et al, 2022). It will parasitize on the 1st day of the fifth instar of the silkworm.…”
Section: Methodsmentioning
confidence: 99%
“…The tachinid parasitoids Exorista japonica (Diptera: Tachinidae), E. sorbillans and Blepharipa zebina (Diptera: Tachinidae) are major larval endoparasites of B. mori and Antheraea pernyi (Lepidoptera: Saturniidae) , causing severe damage to sericulture industry (Dindo & Nakamura, 2018;Jayaram et al, 2014;Rath & Sinha, 2005). We have previously demonstrated that the larval development of B. mori is accelerated, and the expression of NOS in B. mori is up-regulated by E. japonica parasitism (Dai, Yang, et al, 2022;Dai, Ye, et al, 2022), suggesting that NO might be involved in host development, which provides us a good system to study the role of NO in the host under the parasitoid stress. In this study, the effects of E. sorbillans parasitism on host NO production and the role of host NO in E. sorbillans development were investigated.…”
Section: Introductionmentioning
confidence: 99%